Pengaruh Penggunaan Dosis Pupuk NPK 16:16:16 Dan Pupuk Organik Kasgot Biochar Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Putih (Brassica Pekinensis L.) Varietas Itto - Mahdayan Mahdayan; Syarifa Mayly; Ichpan Zulpansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research is to determine the effect of using NPK 16:16:16 fertilizer dosage on the growth and yield of white mustard (Brassica Pekinensis) ITTO variety to determine the effect of using organic kasgot biochar fertilizer on the growth and yield of white mustard (Brassica Pekinensis) ITTO variety of white mustard (Brassica Pekinensis) ITTO variety to determine the interaction between the treatment of 16:16:16 fertilizer dosage and organic kasgot biochar fertilizer on the growth and yield of white mustard (Brassica Pekinensis) ITTO variety.This study was conducted in the land of UPT BIH (Horticulture Parent Seed Task Force Unit) Kutagadung, Berastagi District, Karo Regency, North Sumatra. The study was conducted in November 2023 - December 2023. This study used a factorial randomized block design consisting of two factors, namely: Factor I. Provision of Kasgot Biochar Fertilizer (K) with 4 levels, namely: K0 = Control, K1 = 1 kg / plot, K2 = 2 Kg / plot. Factor II. Application of NPK Fertilizer 16:16:16 (P) with 4 levels, namely N0 = Control N1 = 10 grams/plot, N2 = 20 grams/plot, N3 = 30 grams/plot The results of the study showed that the Use of Kasgot Biochar Fertilizer (K) was significantly different from plant height, plant diameter, leaf width, fresh weight per crop of sample plants, fresh weight of plants per plot and production per hectare. The best treatment was the K2 treatment (2 kg/plot). The use of NPK Fertilizer (N) was significantly different from plant height, plant diameter, leaf width, fresh weight per crop of sample plants, fresh weight of plants per plot and production per hectare. The best treatment of N-P-K 16-16-16 fertilizer was the N3 treatment (30 grams/plot), and the Interaction of the use of Kasgot Biochar Fertilizer (K) and NPK Fertilizer (N) was not significantly different from plant height, plant diameter, leaf width, fresh weight per crop of sample plants, fresh weight of plants per plot and production per hectare.